Inclusão de aditivo Bacillus subtilis e blend de bactérias em dietas para tilápia do Nilo - Silva, Antonio Francisco Campanha da (2020)
The objective is to evaluate the inclusion of two types of commercial probiotics being a blend of bacteria and the other containing only Bacillus Subtillis in diets for Nile tilapia juveniles. The effect of these products on zootechnical performance, hematological parameters, glucose concentration, intestinal villus morphology and histomorphometry of liver hepatocyte nuclei were investigated. 96 juveniles were used, with an initial average weight of 4.87 ± 0.64 g and 6.50 ± 0.2 cm in total length, randomly distributed in 12 tanks with a capacity of 18 L and with eight fish in each experimental unit in a period of 53 days, fed with different treatments: (C) Control; (BB) feed with bacteria blend; (BS) feed with Bacillus subtilis. Between the groups that received and the group that did not receive probiotics did not differ in the zootechnical performance of tilapia-do-Nile however for mean intestinal length there was a difference between the treatments. For the hematological parameters, there was a difference between the groups treated for the number of erythrocytes, where the group treated with BB had the highest values ahead of the control group and the group treated only with BS, but had no change for the other blood parameters. In the analysis of the centesimal composition no significant difference was observed between the treatments. The histomorphometries of intestinal villi were higher for BB in height and width of the villi, but in the thickness of the tunic was higher in the group treated with BS. In the histomorphometric analysis of hepatocyte nuclei, fish treated with BB had higher values for area (μm²), perimeter (μm) and volume (μm³) of nuclei. The probiotics B. subtilis and the bacteria blend, included in the Nile tilapia diet, did not produce significant differences in zootechnical performance, centesimal composition and hematology, but modified the structure of the intestine and liver cells.